Comprehensive analysis of immunological synapse phenotypes using supported lipid bilayers - Valvo, S; Mayya, V; Seraia, E; Afrose, J; Novak-Kotzer, H; Ebner, D; Dustin, M (Humana Press, 2017)
Supported lipid bilayers (SLB) formed on glass substrates have been a useful tool for study of immune cell signaling since the early 1980s. The mobility of lipid-anchored proteins in the system, first described for antibodies binding to synthetic phospholipid head groups, allows for the measurement of two-dimensional binding reactions and signaling processes in a single imaging plane over time or for fixed samples. The fragility of SLB and the challenges of building and validating individual substrates limit most experimenters to ~10 samples per day, perhaps increasing this few-fold when examining fixed samples. Successful experiments might then require further days to fully analyze. We present methods for automation of many steps in SLB formation, imaging in 96-well glass bottom plates, and analysis that enables >100-fold increase in throughput for fixed samples and wide-field fluorescence. This increased throughput will allow better coverage of relevant parameters and more comprehensive analysis of aspects of the immunological synapse that are well reconstituted by SLB.